Application of Maqasid in the Jurisprudence of Minorities: The Case of ‘Zawaj al-Maslahah’ in the West - Rissouni, Kotb; al-Zanki, Najmaldeen K. Kareem (Jurnal Fiqh, 2015)
This study examines the application of Syarī’ah objectives (Maqāsid) to legal questions concerning family law for Muslim minorities. It focuses on Zawāj al-Maslahah/the marriage of convenience, which is present in the West, explains classical forms of marriages resembling it, and elucidates the Muslim response and scholarly Fatwas delivered on this form of marriage. The study relies on a descriptive and analytical method and concludes with several important findings. We conclude that a marriage of convenience resembles the following three types of marriages under scholarly dispute: the enjoyment marriage, marriage with the intention of divorce,and the formal marriage. Nevertheless, the marriage of convenience violates the Maqāsid of Syarī‘ah and trivialises the ideal and ethical aspects of marriage.The authors recommend two different legal decisions concerning this type of marriage based on the Maqāsid. These decisions are to invalidate this marriage before its realisation or to validate it if it has been realised, specifically if the wedding ceremony or sexual intercourse have occurred.